Percepção de profissionais e pacientes de uma enfermaria de pediatria sobre conhecimento e aplicabilidade da segurança do paciente - Oliveira, Andrea Alencar de (2020)
The thematic of patient safety and protection and their implications have been discussed with more attention in recent years. It is estimated that millions of people around world suffer damage, injury or death due to poor health care services or assistance. Policies oriented for a safety culture in health services has been considered a strong indicator of service quality provided. Faced with importance of the theme, the question that guided this study was: What the knowledge of health professionals and assistants/caregivers of pediatric patients (parents/guardians) about the adverse events and how to act in order to improve the patient safety management in children and adolescents? In this way, a field research was conducted, in a pediatric ward, with exploratory, quantitative and descriptive approach. Two forms were applied. Health professionals formed the group 1 (n=40), and responded to the HSOPDC form, based on the Brazilian reality and available for health services usage. The group 1 presented the profile of working in this hospital between 1 and 5 years (57.5%), with a working day between 20 and 39 hours/week (52.5%), complete high school degree (37.5%) and works, mainly, the office of auxiliary nurses (35%), working directly with the patient in their entirety (100%). Most females (87.5%), with an average age of 37 years old. While for the group 2 (n=52), formed by the assistants/caregivers, we applied a custom form, identifying the environment security measures and the knowledge about the patient safety issues. The profile of the group 2 is characterized, in their majority, such as women (80.8%), mother (57.7%) with an average of 31 years old, with the first degree incomplete (57.7%) and resident in the city where the hospital form was applied (Mauá - SP = 69.2%). In this study, several aspects were observed related to safety culture, divided in dimensions and items. Positive and negative responses evaluated, according to the results were statistically significant (p < 0.05). The results found suggest and identify possible failures and contribute to patient safety management in the hospital environment. Finally, it is understood that there is a great requirement to understand what habits should be modified and new routines established. New roles will empower this chain and will practice significant gain in favor of patient safety.